DAMPAK EKONOMI KREATIF, INOVASI PRODUK KULINER, DAN PEMASARAN DIGITAL PADA PENGEMBANGAN BISNIS BERKELANJUTAN DI WISATA KULINER BROMO TENGGER SEMERU (BTS) JAWA TIMUR - Imanuel Billy Andriyanto; Ahmad Dimas Nurfurqon; Irra Chrisyanti Dewi (JURNAL ILMIAH EDUNOMIKA, 2026)
The growth of tourism industry, particularly through creative economy initiatives, plays a key role in boosting local economic development, especially within the culinary sector. Despite its potential, the BTS tourism sector has yet to fully tap into its opportunities. This is evident from the limited innovation in products, the underuse of digital marketing, and the absence of creative economy principles in managing culinary businesses. This research seeks to explore how the creative economy, innovation in culinary products, and digital marketing contribute to the growth of sustainable culinary businesses in the region. This study uses a quantitative approach, applying the PLS-SEM method for analysis. The sample includes 162 culinary business owners, chosen using purposive sampling. The data was gathered using questionnaires and then analyzed by evaluating both the measurement model (outer model) and the structural model (inner model). This included testing for validity, reliability, the coefficient of determination (R²), and hypothesis testing. The findings show that the creative economy, innovation in culinary products, and digital marketing play a crucial and positive role in the growth of sustainable culinary businesses. The creative economy stands out as the leading factor, with a coefficient of 0.385, followed closely by digital marketing at 0.352, and culinary product innovation at 0.214. Additionally, the research model shows a robust predictive power, with an R² value of 0.781 and a Q² value of 0.584, suggesting that these independent variables account for a significant portion of the variance in the development of sustainable businesses. These findings highlight that the synergy between creativity, product innovation, and the utilization of digital technology is essential in creating adaptive, competitive, and sustainable culinary businesses in the BTS tourism area.